Effect of Large Scale 3-D Structures on the Flow Around a Heated Cylinder at Low Reynolds Number - Stefano Rolfo; Konstantinos Kopsidas; Shahnurriman A. Rahman; Charles Moulinec; David R. Emerson (Springer Nature Switzerland, 2024)
Volume:101